Introduction of foreign metals onto unsupported and supported nickel praseodymium oxide catalyst for conversion of carbon dioxide to methane - Mohd. Marsin, Faridah (2006)
Nickel oxide based catalysts have long been known as one of the most used based materials applied for various catalyst developments. Researchers nowadays are trying to emerge with a suitable method to enhance the NiO catalyst capability for the benefit of the industries. It was observed that by introducing foreign metals with an optimized condition will increase the catalyst capability. In this study, a catalyst has been succesfully developed that can potentially be used for natural gas purification where CO2 is catalytically converted to methane. A screening test was performed in the hope to find a suitable dopant for NiO catalyst. Seven chosen metals, M*; Mg, Zr, Mo, Mn, Fe, Co, and Cu, with a required addition of Pr from the lanthanide series was incorporated into NiO based catalyst in the weight ratio of (60% Ni: 30% M*: 10% Pr) and (60% Ni: 10% M*: 30% Pr). All prepared catalysts were aged for one day and calcined for 17 hours before tested for its ability to remove CO2 using a home-built reactor. In assistance of X-ray Diffraction (XRD) and X-ray Photoelectron Spectroscopy (XPS) analysis, Scanning Electron Microscopy (SEM), nitrogen adsorption, single point BET and Fourier Transformed Infra Red analysis (FTIR) were also carried out to reinforce the results. It was found that the incorporation of Co and Pr enhances the catalytic performance by full removal of CO2 as well as producing methane at a low temperature of 330Â°C. Optimization on the ratio was carried out and was catalytically tested. From the characterization of the best catalyst, the XRD results showed that the catalyst formed individual phases of NiO, Co3O4 and PrO2, while SEM assigned the presence of small particles that homogeneously distributed. The study was continued using support for the Ni/Co/Pr catalyst, whereby three supports were chosen; alumina beads (Al2O3), molecular sieve (Na12[(AlO2)12]5SiO. x H2O), and cordierite (2MgO- 2Al2O3-5SiO2). Adsorption and impregnation method was used in coating the catalyst onto the support. Verifications have been made to optimize the preparation conditions; catalyst loading, time of dipping, ratio of catalyst, calcination temperature, and addition of binder. Results showed the most favorable support for Ni/Co/Pr catalyst was cordierite. From the catalytic activity, the optimum catalyst ratio for the supported catalyst was 60:35:5, and the best possible catalyst loading onto the cordierite is approximately 25 %. The optimum calcination temperature was at 400Â°C for 17 hours as concluded from the XRD analysis. However as the conversion of CO2 to methane was extended for another 10 hours on stream test, it appeared that the catalytic performance declined. The decrease from a maximum of a 100 % of CO2 conversion to 60 % conversion gave a lot of impact. From the XPS study it was found that throughout the stages of catalytic testing, the oxidation state of the individual phases changed from Ni2+ to Ni3+, and from mixture of Co2+ and Co3+ to completely Co2+. This finding was backed up by XRD analysis that also confirmed the changing of oxidation state. The changing of oxidation state in metal in supported catalyst resulted in rapid deactivation of catalytic performance that shortened the life span of the catalyst. The performance of the catalyst also declined as it was exposed to H2S.